Thrombin Generation in Fresh and Frozen-Thawed Platelet Poor Plasma - Is there a Difference? - Kausche, Lea Elisabeth; Adler, Werner; Zimmermann, Robert; Hackstein, Holger; Strasser, Erwin (Clinical Laboratory, 2020)
Background: Applicability of thrombin generation tests to clinical routine has been sought for many years. The aim of this study was to compare thrombin generation measured in fresh platelet poor plasma (f-PPP) and frozen-thawed platelet poor plasma (ft-PPP) to prove the consistency of results.
CRIS-Team WoS Importer:2020-07-17